Ceramics and Atlantic connections : late Roman and early medieval imported pottery on the Atlantic seaboard : international symposium, Newcastle University, March 26th-27th 2014 - Duggan, Maria; Duggan, Maria; Turner, Sam; Turner, Sam; Jackson, Mark; Jackson, Mark (Roman and late antique Mediterranean pottery, 2020)
Papers focus on the pottery of Mediterranean origin imported into the Atlantic, as well as ceramics of Atlantic production which had widespread distribution. They examine chronologies and relative distributions, and consider the composition of key Atlantic assemblages, revealing new insights into the networks of exchange between c. 400-700 AD